The importance of work spirituality and the role of Lmx on performance - Nidya Banuari; Manda Dwipayani Bhastary; Emma Novirsari; Dewi Rafiah Pakpahan; Stevan Rejekiman Gea (Institute of Computer Science (IOCS), 2023)
Aceh Regional Secretariat is one of the Aceh Apparatus Work Units playing a role in supporting the improvement of Mandated Governance (Performance Report of Aceh Regional Secretariat, 2020). This achievement is carried out through the implementation of various programs and activities according to the Strategic Plan of Aceh Regional Secretariat and Rencana Pembangunan Jangka Menengah Aceh (RPJMA). However, in the implementation of its current activities, it is inseparable from various obstacles in improving its performance. Based on the description of previous research and because there are still differences in research results in the literature about the influence of LMX on performance, it is necessary to produce a new study to produce a clearer understanding for literature enrichment and also fill in the gaps that have occurred so far. This study wants to see the overall influence of LMX variables and work spirituality on the performance of employees of the Aceh Regional Secretariat. In this study, researchers used a descriptive method. Leader-member exchange and work spirituality has a positive and significant effect on the performance of employees of the Regional Secretariat of Aceh Province.